2017
DOI: 10.3389/fnhum.2017.00071
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Human Trials of Transcranial Direct Current Stimulation between 1960 and 1998

Abstract: Background: Transcranial direct current stimulation (tDCS) is investigated to modulate neuronal function including cognitive neuroscience and neuropsychiatric therapies. While cases of human stimulation with rudimentary batteries date back more than 200 years, clinical trials with current controlled stimulation were published intermittently since the 1960s. The modern era of tDCS only started after 1998.Objectives: To review methods and outcomes of tDCS studies from old literature (between 1960 and 1998) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…However, rodent studies typically use ten-fold stronger current intensities compared to human studies 66 . Across the 28 rodent experiments reviewed 67 (Supplementary Table 2), the induced intracranial fields averaged 6.8 ± 3.8 V/m ( n = 11, ten epicranial and 1 subdural studies), compared to < 1 V/m measured in conventional human TES studies 19 , 68 , 69 .…”
Section: Acute Effects Of External Electric Fields In Rodentsmentioning
confidence: 99%
“…However, rodent studies typically use ten-fold stronger current intensities compared to human studies 66 . Across the 28 rodent experiments reviewed 67 (Supplementary Table 2), the induced intracranial fields averaged 6.8 ± 3.8 V/m ( n = 11, ten epicranial and 1 subdural studies), compared to < 1 V/m measured in conventional human TES studies 19 , 68 , 69 .…”
Section: Acute Effects Of External Electric Fields In Rodentsmentioning
confidence: 99%
“…tDCS protocols in humans circa 1970 used relatively low current intensities but with smaller electrodes and longer durations than are common today, resulting in cases of electrode charge density >100 kC/m 2 , with no reports of lasting side-effects [8]. It would be unreasonable to apply only electrode charge density-safety threshold values from rodent studies (using small epicranial electrodes) as evidence these tDCS protocols were in fact injurious.…”
Section: Dear Editormentioning
confidence: 99%
“…In 16 healthy participants 3 mA tDCS, with topical anesthetic cream, was tolerated and produced intensity-specific neuromodulation [8]. A review of early evaluations of tDCS circa 1960 identified a single instance of 3 mA, with local anesthetic used [9]. High-definition tDCS (HD-tDCS) was tolerated at 3 mA [10] in a sample of older adults.…”
Section: Introductionmentioning
confidence: 99%